Perceptions of primary healthcare nurses about the effectiveness of their working environment for integrated primary healthcare service delivery in Nelson Mandela Bay Health District - Baartman, Zubrina (Stellenbosch : Stellenbosch University, 2024)
Thesis (MNur)--Stellenbosch University, 2024.